2016
DOI: 10.1038/ncomms13336
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic regulation of chondrocytes by Rela through induction of anti-apoptotic and catabolic target genes

Abstract: In vitro studies have shown that Rela/p65, a key subunit mediating NF-κB signalling, is involved in chondrogenic differentiation, cell survival and catabolic enzyme production. Here, we analyse in vivo functions of Rela in embryonic limbs and adult articular cartilage, and find that Rela protects chondrocytes from apoptosis through induction of anti-apoptotic genes including Pik3r1. During skeletal development, homozygous knockout of Rela leads to impaired growth through enhanced chondrocyte apoptosis, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 46 publications
1
87
0
3
Order By: Relevance
“…Rela is the key subunit of the NF-ĸB family [31]. Rela/p65 plays an essential role in the process of mediating NF-κB signaling and is involved in chondrogenic differentiation, cell survival and catabolic enzyme production [31]. Tumor necrosis factor receptor-associated factor 3 (Traf3) can activate NF-κB through both canonical and non-canonical signaling pathways [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rela is the key subunit of the NF-ĸB family [31]. Rela/p65 plays an essential role in the process of mediating NF-κB signaling and is involved in chondrogenic differentiation, cell survival and catabolic enzyme production [31]. Tumor necrosis factor receptor-associated factor 3 (Traf3) can activate NF-κB through both canonical and non-canonical signaling pathways [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The NF-κB family of transcription factors plays important roles in a wide range of biological processes such as inflammation, immune responses, cell proliferation, cell differentiation, cell survival and apoptosis [30,31]. Rela is the key subunit of the NF-ĸB family [31]. Rela/p65 plays an essential role in the process of mediating NF-κB signaling and is involved in chondrogenic differentiation, cell survival and catabolic enzyme production [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each zone contains chondrocytes at different stages of differentiation. For example, p65 expression is observed throughout the growth plate, but mainly in the resting and hypertrophic zones, suggesting that the classical NF-κB pathway is involved in normal bone development, particularly endochondral ossification [7,10]. Overexpression of a dominant negative form of IκBα that blocks NF-κB activation leads to abnormal limb bud development and downregulation of BMP signaling in chicken embryos [15].…”
Section: The Role Of the Classical Nf-κb Pathway In Chondrogenic Devementioning
confidence: 99%
“…The transcription factor nuclear factor-κB (NF-κB) regulates the expression of a wide variety of genes involved in immune and inflammatory responses, cell proliferation, tumorigenesis, cell survival, and development [5,6]. Several studies have reported that the NF-κB transcription family is involved in endochondral ossification and limb outgrowth under physiological conditions [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%